Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Terhadap Hasil Belajar Siswa Pada Materi Bentuk Aljabar Di Kelas VII SMP Negeri 3 Tondano - Ira Elika Mandiangan; John Robby Wenas; Helen Yuliana Angmalisan (Journal on Education, 2025)
This study aimed to determine whether the implementation of Team Assisted Individualization (TAI) cooperative learning model has an effect on students’ learning outcomes on the algebraic expression material in the 7th grade at SMP Negeri 3 Tondano. The research method used was a quasi-experimental research type with two groups of subjects, namely class VIIA with 26 students as the experimental class and class VIIB with 23 students as the control class at SMP Negeri 3 Tondano. This study used the pretest and posttest control group design with data collection techniques using learning outcomes tests, which were then analyzed by conducting a t-test. Based on the t-test calculation, it obtained tobtained>ttable = 2.613 > 2.012, thus reject H0 and accept H1. This means that the average learning outcomes of experimental class students taught using the TAI cooperative learning model are higher than the average learning outcomes of control class students taught using conventional learning models.